2020
DOI: 10.1021/acsenergylett.0c00532
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the Electrocatalyst–Ionomer Interface via Sulfonated Poly(ionic liquid) Block Copolymers to Enable High-Performance Polymer Electrolyte Fuel Cells

Abstract: Polymer electrolyte membrane fuel cell (PEMFC) electrodes with a 0.07 mg Pt cm −2 Pt/Vulcan electrocatalyst loading, containing only a sulfonated poly(ionic liquid) block copolymer (SPILBCP) ionomer, were fabricated and achieved a ca. 2× enhancement of kinetic performance through the suppression of Pt surface oxidation. However, SPILBCP electrodes lost over 70% of their electrochemical active area at 30% RH because of poor ionomer network connectivity. To combat these effects, electrodes made with a mix of Naf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 52 publications
1
59
0
Order By: Relevance
“…Some ILs possess excellent oxygen solubility and diffusivity, although not as good as Nafion ionomer, they can penetrate the small pores that cannot be reached by the large ionomer cluster thus enhancing catalyst utilization ratio. Li et al [69] introduced a sulfonated poly(ionic liquid) block copolymer (SPILBCP) as an additive to Nafion ionomer in the catalyst layer. From an electrode structure point of view illustrated in Fig.…”
Section: Other Proton Conductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some ILs possess excellent oxygen solubility and diffusivity, although not as good as Nafion ionomer, they can penetrate the small pores that cannot be reached by the large ionomer cluster thus enhancing catalyst utilization ratio. Li et al [69] introduced a sulfonated poly(ionic liquid) block copolymer (SPILBCP) as an additive to Nafion ionomer in the catalyst layer. From an electrode structure point of view illustrated in Fig.…”
Section: Other Proton Conductorsmentioning
confidence: 99%
“…This resistance can be significantly reduced by improving the ionomer distribution to form a homogeneous thin layer on the catalyst surface. Potential strategies include modifying the catalyst support (e.g., NH 3 or N-groups functionalizing carbon support), using SSC ionomer or even combining with ILs, [12,64,69,80] which have been discussed in Sect. 2.…”
Section: Diffusion Principles In Catalyst Layersmentioning
confidence: 99%
“…Most recently, an attempt on implementation of ILs in MEAs was made by Neyerlin et al., who studied the MEA performance of Pt/C catalyst in presence of a sulfonated poly IL block copolymer (SPILBCP). [ 117 ] First, they found that the SPILBCP can replace the conventional Nafion as an ionomer, and the fabricated MEA (Nafion‐free) exhibited a two times higher specific activity (@0.9 V) relative to that using pristine Pt/C catalyst, which was comparable to that obtained using RDE. The IL boosting effect was assumed to benefit from the suppressed formation of Pt oxide in the presence of the IL.…”
Section: Scill Concept In Electrocatalysismentioning
confidence: 99%
“…Apart from tuning the active sites, the Pt-electrolyte interface has an important role in ORR. 21,22 A hydrophobic ionic liquid (IL) modification of Pt surface has recently emerged as another method to enhance the activity of Pt-based catalysts for ORR. [23][24][25] Many groups have investigated the ability of IL modifications to enhance ORR activity with a variety of IL.…”
Section: Introductionmentioning
confidence: 99%